Occupational burnout and empathy influence blood pressure control in primary care physicians - Oriol Yuguero; Josep Ramon Marsal; Montserrat Esquerda; Jorge Soler-González (BMC Family Practice, 2017)
Abstract Background Good physician-patient communication can favor the adoption of healthy lifestyle habits, which is essential in high blood pressure (BP) management. More empathic physicians tend to have lower burnout and better communication skills. We analyzed the association between burnout and empathy among primary care physicians and nurses and investigated the influence on BP control performance. Methods Descriptive study conducted in 2014 investigating burnout and empathy levels in 267 primary care physicians and nurses and BP control data for 301,657 patients under their care. We administered the Maslach Burnout Inventory and the Jefferson Scale of Physician Empathy and defined good BP control as a systolic BP <130 mmHg. Results Low burnout and high empathy were observed in 58.8% and 33.7% of practitioners, respectively. Burnout and empathy were significantly negatively associated (p < 0.009). Practitioners with high empathy and low burnout had significantly better BP control and performance than those with low empathy and high burnout (p < 0.05). Conclusions Low burnout and high empathy were significantly associated with improved BP control and performance, possibly in relation to better physician/nurse-patient communication.